Contemporary mass balance on a cold Eastern Alpine ice cap asa potential link to the Holocene climate - Fischer A.; Stocker-Waldhuber M.; Frey M.; Bohleber P. (Scientific Reports, 2022)
Alpine cold ice caps are sensitive indicators of local climate. The adequate interpretation of this information in an ice core requires detailed in situ glaciological and meteorological records, of which there are few. The Weißseespitze summit ice cap (3499m) presents an ideal case to compare past and present climate and mass balance, with limited ice flow, but close to 6000years locked into about 10m of ice. First-ever meteorological observations at the ice dome have revealed that over 3years of observation most of the accumulation took place between October and December and from April to June. In the colder winter months, between January and March, wind erosion prevents accumulation. Melt occurred between June and September, ice was only affected during short periods, mainly in August, which caused ice losses of up to 0.6m (i.e. ~ 5% of the total ice thickness). Historical data points at a loss of of 34.9 ± 10.0m between 1893 and 2018 and almost balanced conditions between 1893 and 1914. The local evidence of ice loss lays the basis for the interpretation of past gaps in the ice core records as past warm/melt events.